PENGELOMPOKAN SUSU BAYI DAN SUSU BALITA BERDASARKAN KOMPOSISI NILAI GIZI DENGAN METODE ANALISIS KOMPONEN UTAMA DAN ANALISIS GEROMBOL (Universitas PGRI Sumatera Barat, 2011)
This research is done for baby milk, balita's milk, and child milk bases circulatingage category at marketing bases to usufruct registry at Ramayana Department StoreMoorland. Result agglomeratedding to give picture to society in particular mother to getmilk for their child at the price that achievable. Data is analysed by use of Cluster Analysisgets merging hierarchy with Euclid's distance square as size as differentiable. Distancesremedial method which be utilized is Ward's method. Before done by Cluster Analysis,need to be done by Principal Components Analysis because of high correlation amongvariable. The result from Principal Components Analysis will be new variablerepresentatively diversity of origin variable which doesn’t have correlation any more.Acquired result is consisting of 3 clusters to baby milks, where is Frisian Flag's milk(cluster 1), SGM 2 (cluster 2), and Frisian Flag Full Cream (cluster 3) are milk that itslower price with the same nutrient composition, 3 clusters to balita's milks, where is SGM 3Honeys (cluster 1), Vitalac 3 Honeys, Vitalac 3 Vanilla (cluster 2), Indomilk Bio Kids,Frisian Flag Full Cream, and Dancow 1 + Chocolates (cluster 3) are milk that lower pricewith the same nutrient composition, 4 clusters to baby milks, where is Dancow 3 + Vanilla(cluster 2), SGM 4 (cluster 3), and Frisian Flag (cluster 4) are milk that its lower price withsame nutrient composition.